THE EFFECT OF USING PORPE METHOD IN COMPREHENDING NARRATIVE READING TEXT OF THE TENTH GRADE STUDENTS OF SMK MUHAMMADIYAH 2 PEKANBARU - Viona Purba; Novitri Novitri; Maria Safriyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to find out the significant effect of PORPE Method in comprehending narrative reading text of the tenth grade students of SMK Muhammadiyah 2 Pekanbaru. The selected sample was X OTKP 1. The sample was selected by using random sampling technique. This research used pre-experimental research design for one group pre-test post-test and collected the data by using test on narrative text. The test this research was multiple choice test consisted of four option (A/B/C/D) The result of the study was found that the mean score of the pre-test was 68.64 while the post-test was 75.61 Therefore it can be concluded that there is a significant effect of PORPE Method in comprehending narrative reading text of the tenth grade students of SMK Muhammadiyah 2 Pekanbaru. Based on the result of data analysis, it can be concluded that there is a significant effect in students’ achievement before and after being thought by PORPE Method. It can be stated that the alternative hypothesis (Ha) is accepted. In conclusion, teachers are suggested to use PORPE Method as one of the alternative method in improving students’ reading comprehension especially in comprehending narrative texts.    Key Words: Effect, PORPE method, Reading Comprehension, Narrative Text